A comparative analysis of mammography breast imaging reporting and data system score and fine needle aspiration cytology in the evaluation of palpable breast lump - Pandia, Arpita; Samantaray, Sagarika; Mohapatara, Jay Sonali; Dash, Sashibhusan (International Journal of Research in Medical Sciences, 2019)
Background: Breast lump is one of the commonest complaints with which patients present in breast clinics. As in most cases breast lump ultimately leads to a diagnosis of breast cancer, it is important for women with a breast lump to receive appropriate evaluation. So initial diagnostic approach such as utilization of rapid, inexpensive, presumptive and safe method is utmost important as such methods not only would benefit both patients and clinicians by prompting proper preoperative diagnosis and management but also further limits unnecessary testing and procedures. Aim and objectives of this study was to analyse the diagnostic accuracy of mammogram according to Breast Imaging Reporting and Data System (BI-RADS) score and fine-needle aspiration cytology (FNAC) in patients presented with benign and malignant breast lumps in authors centre. Methods: During this retrospective study from January 2018 to December 2018, the subjects concerned included all the female patients, who were referred to the department of pathology for FNAC of their breast mass and had radiological reports (mammography) with BI-RADS score according to the latest guidelines. The sensitivity, specificity, accuracy, positive and negative predictive values of BI-RADS scores and FNAC in diagnosis of breast diseases was done on the basis of final diagnosis. Results: In this study, the sensitivity, specificity, positive predictive value, negative predictive value and accuracy was 88.57%, 82.46%,75.61%,92.16% and 84.78%, respectively for Mammography (BIRADS) score and 100% for all the parameters on FNAC. Conclusions: According to authors above study findings concluded that FNAC could be considered an ideal initial diagnostic modality in all breast lumps recognized by means of imaging techniques. It is not only considered as safe, cost effective, rapid and presumptive diagnostic method but also further limits unnecessary testing and procedures.